Al-Taʿrīb ʿinda al-Qudamāʾ wa al-Muḥdathīn (Dirāsah Waṣfiyyah Muqāranah) - Tyas Pharadita Astari (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2014)
Arabization (taʿrīb) refers to the process of lexical borrowing between Arabic and other languages. This phenomenon has existed since the pre-Islamic period and continues to the present day. Linguists have differed in their views regarding the occurrence and legitimacy of lexical borrowing into Arabic. Some scholars have accepted its existence, while others have rejected it. As the process of lexical borrowing evolved, different scholars developed their own methodologies for adapting foreign words into Arabic. Consequently, significant scholarly debate emerged, leading to the development of two major schools of thought: the classical scholars and the modern scholars. However, the differences between these two groups are not entirely contradictory. Rather, they share several common principles and methodologies in the process of Arabization while differing in other aspects. This article presents a descriptive comparative study of the approaches adopted by classical and modern linguists toward the Arabization of foreign vocabulary.